Explaining Youth Unemployment in Malaysia. The Auto-Regressive Distributive Lag (ARDL) Approach - Che-Yahya, Norliza; Rosdi, Nur Ernisha Anis Suraya Mohd; Zaghlol, Azlul Khalilah; Alyasa-Gan, Siti Sarah (Advances in Social Sciences Research Journal, 2024)
This study examines the influence of macroeconomic factors, namely Gross Domestic Product (GDP), Inflation, Population and Foreign Direct Investment (FDI) on Youth Unemployment in Malaysia from 1991 to 2021 using time series analysis. The data was obtained from World Bank Data and analyzed using EViews software. The time series data was conducted using the Augmented Dickey-Fuller (ADF) test. The Auto-Regressive Distributive Lag (ARDL) approach to cointegration was then employed to determine the short- and long-term analysis of the series. The ARDL bound test analysis indicates that there is a cointegration relationship between macroeconomic factors and youth unemployment. The results suggest that economic growth, inflation, and population have a negative and significant impact on youth unemployment, while foreign direct investment has a positive but insignificant effect on youth unemployment in the long term. Upon analyzing the short-term outcome, it was observed that all factors exhibited a negative correlation and exerted a substantial impact on youth unemployment’s rate.